2010
DOI: 10.1242/jcs.047878
|View full text |Cite
|
Sign up to set email alerts
|

Integrins stimulate E-cadherin-mediated intercellular adhesion by regulating Src-kinase activation and actomyosin contractility

Abstract: Cadherins and integrins are major adhesion molecules regulating cell-cell and cell-matrix interactions. In vitro and in vivo studies have demonstrated the existence of crosstalk between integrins and cadherins in cell adhesion and motility. We used a dual pipette assay to measure the force required to separate E-cadherin-producing cell doublets and to investigate the role of integrin in regulating the strength of intercellular adhesion. A greater force was required to separate cell doublets bound to fibronecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(80 citation statements)
references
References 95 publications
3
77
0
Order By: Relevance
“…Inhibition of events downstream of β1‐integrin binding to laminin 511, including inhibition of focal adhesion kinase and Src kinase (Martinez‐Rico et al , 2010), also reduced the cell–cell adhesion strengths (Fig 5D). Similarly, inhibition of RhoA signalling, which has been implicated in both VE‐cadherin junctional localization and can also occur downstream of laminin–β1 integrin‐mediated interactions (Yamamoto et al , 2015), significantly reduced cell–cell adhesion strengths (Fig 5D).…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…Inhibition of events downstream of β1‐integrin binding to laminin 511, including inhibition of focal adhesion kinase and Src kinase (Martinez‐Rico et al , 2010), also reduced the cell–cell adhesion strengths (Fig 5D). Similarly, inhibition of RhoA signalling, which has been implicated in both VE‐cadherin junctional localization and can also occur downstream of laminin–β1 integrin‐mediated interactions (Yamamoto et al , 2015), significantly reduced cell–cell adhesion strengths (Fig 5D).…”
Section: Resultsmentioning
confidence: 83%
“…Cells attached to beads were then permitted to bind to each other, and the strength required to detach two cells was measured (cell–cell adhesion strength). Previous studies have shown that adhesion complexes form in cells bound to the ECM‐coated beads (Martinez‐Rico et al , 2010). It was not possible to measure cell–cell adhesion strength after adhesion to laminin 411 due to the weak adhesion of HUAECs to this laminin isoform.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Comprised of one α‐ and one β‐subunit, integrins bind with variable affinity and avidity to specific ECM proteins to provide anchorage and activate pro‐survival signalling 8. Intercellular adhesion mediated by integrins has also been described in squamous epithelium 16, 17, and the presence of integrin‐α 2 , α 3 , α 6 and α v has been demonstrated in oesophageal squamous epithelium 18, 19, 20. These adhesion molecules are constantly recycled in order to facilitate tissue remodelling in response to physiological stress.…”
Section: Introductionmentioning
confidence: 99%